2006
DOI: 10.1007/s00535-006-1849-3
|View full text |Cite
|
Sign up to set email alerts
|

An audit of the outcome of long-term biliary stenting in the treatment of common bile duct stones in a general hospital

Abstract: Long-term biliary stenting is a feasible option for patients who decline or are medically unfit for further elective endoscopic or surgical procedures. Close follow-up is mandatory to detect and treat late complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 37 publications
1
39
0
1
Order By: Relevance
“…This result is in agreement with data reported from a Japanese study in which 13% of patients suffered cholangitis during biliary stenting [23] . Comparing this with long-term biliary stenting, Ang et al [24] reported up to 22% mortality among patients treated by long-term biliary stenting for an average of 12 mo (range: 1-54 mo), which accounted for 3.5% of biliary-related mortality. However, there was no mortality in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in agreement with data reported from a Japanese study in which 13% of patients suffered cholangitis during biliary stenting [23] . Comparing this with long-term biliary stenting, Ang et al [24] reported up to 22% mortality among patients treated by long-term biliary stenting for an average of 12 mo (range: 1-54 mo), which accounted for 3.5% of biliary-related mortality. However, there was no mortality in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…If general condition of patients permits, periodical stent exchange seems desirable. Although the optimal exchange interval has not been established, annual exchange may be acceptable because Ang et al (22) reported in their review article that the mean duration of stent patency was 12.4 months. Our results support this interval.…”
Section: Discussionmentioning
confidence: 99%
“…2,[5][6][7][8][9][10][11][12][13] In those difficult cases, placement of temporary biliary endoprotheses to maintain adequate biliary drainage have been used as a bridge to subsequent interventions. [14][15][16][17] The use of covered self-expandable metal stents (CSEMSs) in benign disease is increasing, but few have explored their role in complex stone cases. Based on previous use, it can be hypothesized that CSEMSs could have an advantage over plastic stents in improving subsequent duct clearance.…”
mentioning
confidence: 99%